2021
DOI: 10.1186/s40824-021-00229-3
|View full text |Cite
|
Sign up to set email alerts
|

Polyphenols-loaded electrospun nanofibers in bone tissue engineering and regeneration

Abstract: Bone is a complex structure with unique cellular and molecular process in its formation. Bone tissue regeneration is a well-organized and routine process at the cellular and molecular level in humans through the activation of biochemical pathways and protein expression. Though many forms of biomaterials have been applied for bone tissue regeneration, electrospun nanofibrous scaffolds have attracted more attention among researchers with their physicochemical properties such as tensile strength, porosity, and bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 108 publications
0
16
0
Order By: Relevance
“…3 Regards, electrospun nanofibrous scaffolds have recently attracted considerable attention for bone tissue engineering due to the structural similarity to the natural ECM, lower production price, ability to use various materials, easy operation, and controllable process to modify the morphology and diameter of fibers. 4,5 Polycaprolactone (PCL) is a soft, aliphatic, and semicrystalline polyester which shows high solubility in organic solvents at low temperatures. 6 This nontoxic polymer is biodegradable through hydrolysis in the natural environment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Regards, electrospun nanofibrous scaffolds have recently attracted considerable attention for bone tissue engineering due to the structural similarity to the natural ECM, lower production price, ability to use various materials, easy operation, and controllable process to modify the morphology and diameter of fibers. 4,5 Polycaprolactone (PCL) is a soft, aliphatic, and semicrystalline polyester which shows high solubility in organic solvents at low temperatures. 6 This nontoxic polymer is biodegradable through hydrolysis in the natural environment.…”
Section: Introductionmentioning
confidence: 99%
“…In most cases, bone repairing is a high cost and longtime treatment, so using reconstructive medicine like temporary and permanent tissue replacements has become very common especially in severe injuries 3 . Regards, electrospun nanofibrous scaffolds have recently attracted considerable attention for bone tissue engineering due to the structural similarity to the natural ECM, lower production price, ability to use various materials, easy operation, and controllable process to modify the morphology and diameter of fibers 4,5 …”
Section: Introductionmentioning
confidence: 99%
“…1 and 2 ). According to the Raman spectra, the I D /I G ratio revealed that rGO was successfully synthesized without the use of toxic chemicals; instead, we utilized a phytochemical (EGCG), one of the most abundant polyphenols found in green tea [ 43 ], in the reduction step. The I 2D /I G ratio of less than 1 indicates a multi-layered graphitic structure with the presence of few defect sites, revealed by a less intensity of the 2D band to G band [ 25 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…where λ = 2πλ ≈ (37.1 ± 14.1) m −1 [63]. The initial condition for this non-linear ordinary differential equation is u(0) = r 6 (0) (12) This condition represents the initial spherical drop in contact with the substrate. Practically, in most experiments of contact angle cases, the initial condition should start with a finite contact width r 0 ; therefore, the initial condition is u(0) = (r(0)) 6 = (r 0 ) 6 (13)…”
Section: Estimation Of the Interfacial Energy By Water Contact Testmentioning
confidence: 99%
“…Slowly degradable polyphenols can be coated on orthopedic implants to promote bone regeneration. When added to nanofiber scaffolds, polyphenols even showed some antioxidant effects [12]. Silk fibroin nanofibers, a complicated natural hydrogel, are a respectable constituent in artificial skin, considering their exceptional biocompatibility [13].…”
Section: Introductionmentioning
confidence: 99%